Hemophilia care in China: review of care for 417 hemophilia patients from 11 treatment centers in Shanxi Province. Issue 4 (August 2015) - Zhao, Hua; Yang, Linhua; Long, Chao; Guo, Yulin; Wu, Ruihong; Liu, Xiue; Qin, Xiuyu; Liang, Hongzheng; Duan, Zhiguang
Abstract : Aims: We analyzed the clinical features of 417 patients with hemophilia from 11 Hemophilia Treatment Centers in Shanxi Province (SP) in China. Methods: We used data collected in the national registry of hemophilia A and hemophilia B in SP from January 2010 to December 2013. Results: Ratio of hemophilia A:hemophilia B patients was 5:1, of which 48% (200/417) were severe, 31% (129/417) moderate and 21% (88/417) mild. Episodes of joint bleeding occurred in 73% (305/417) of patients. Only 4% (15/417) of patients received tertiary prophylaxis. Three percent of patients (2/72) were hepatitis B virus-Ab positive, and 7% (5/72) of patients were hepatitis C virus-Ab positive. The incidence of inhibitors was 6% (11/182). Conclusion: The ability to manage hemophilia in SP remains suboptimal. However, due to limited data, the evaluation and extrapolation of large hemophilia populations in SP are restricted, therefore, further studies with a large cohort are needed.